2023
DOI: 10.1021/acsami.3c14054
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Colorful Ultralong Organic Room-Temperature Phosphorescence by Precise Modification of Nitrogen Atoms on Phosphorescence Units

Huiwen Jin,
Xue Zhang,
Jiaxin Ma
et al.

Abstract: We successfully tune ultralong organic room-temperature phosphorescence (UORTP) by a simple strategy of precisely modifying nitrogen atoms on Phosphorescence Units, and colorful ultralong phosphorescence can be achieved. We for the first time investigate the structure–function relationship between phosphorescence properties and molecular structures of Phosphorescence Units. With BCz and BCz-1 as comparison, eight new Phosphorescence Units were synthesized by introducing one or two nitrogen atoms to the naphtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…As for the mechanism of photoinduced UORTP color change, we deduced that NBCz units might undergo chemical reaction and molecular structure change under continuous UV irradiation. First, we revisited our previous work where eight new phosphorescence units were obtained by modification of nitrogen atoms. The UORTP color was unchanged for all other seven molecules after prolonged UV irradiation, suggesting that photoinduced UORTP color change is an exclusive property for NBCz.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…As for the mechanism of photoinduced UORTP color change, we deduced that NBCz units might undergo chemical reaction and molecular structure change under continuous UV irradiation. First, we revisited our previous work where eight new phosphorescence units were obtained by modification of nitrogen atoms. The UORTP color was unchanged for all other seven molecules after prolonged UV irradiation, suggesting that photoinduced UORTP color change is an exclusive property for NBCz.…”
Section: Resultssupporting
confidence: 64%
“…After 5 s UV irradiation (Figure a), a yellowish-green afterglow came out, and the phosphorescence bands were located at 525 (τ = 387.85 ms), 571 (τ = 366.85 ms), and 621 nm (τ = 369.08 ms) (Figure b,e), which was totally different from those of PCBNBCz and FSO 2 NBCz. In our previous work, it is confirmed that these phosphorescence bands are assigned to the intrinsic monomer phosphorescence of N 2 BCz. Thus, the intrinsic monomer phosphorescence of the NBCz units was screened by N 2 BCz units.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations